Regulation of Hyaluronan Synthesis in Vascular Diseases and Diabetes. (5th March 2015) - Moretto, Paola; Karousou, Evgenia; Viola, Manuela; Caon, Ilaria; D'Angelo, Maria Luisa; De Luca, Giancarlo; Passi, Alberto; Vigetti, Davide
Abstract : Cell microenvironment has a critical role determining cell fate and modulating cell responses to injuries. Hyaluronan (HA) is a ubiquitous extracellular matrix glycosaminoglycan that can be considered a signaling molecule. In fact, interacting with several cell surface receptors can deeply shape cell behavior. In vascular biology, HA triggers smooth muscle cells (SMCs) dedifferentiation which contributes to vessel wall thickening. Furthermore, HA is able to modulate inflammation by altering the adhesive properties of endothelial cells. In hyperglycemic conditions, HA accumulates in vessels and can contribute to the diabetic complications at micro- and macrovasculature. Due to the pivotal role in favoring atherogenesis and neointima formation after injuries, HA could be a new target for cardiovascular pathologies. This review will focus on the recent findings regarding the regulation of HA synthesis in human vascular SMCs. In particular, the effects of the intracellular HA substrates availability, adenosine monophosphate-activated protein kinase (AMPK), and protein O-GlcNAcylation on the main HA synthetic enzyme (i.e., HAS2) will be discussed.